Prevalence, risk factors and impact of proteinuria-associated hypomagnesemia in chronic kidney disease patients: cross-sectional study - Ayman Riyadh Abdel-Hameed; Mohammed Fouad Ahmed; Amr Ahmed Elsantawy; Maher Borai Mohammad (SpringerOpen, 2022)
Abstract Background Hypomagnesemia is a predictor of progression and mortality of chronic kidney disease (CKD) patients. However, limited data is available about the prevalence and kidney-related risk factors of hypomagnesemia in the CKD patients. We aimed to investigate the prevalence and risk factors of low serum magnesium level associated with proteinuria and its impact on CKD patients. This cross-sectional study enrolled 100 CKD patients with different stages according to estimated glomerular filtration rate (eGFR), divided into 2 groups (proteinuric and non-proteinuric) in the period from February 2020 to August 2020. Results The number of participants in this study was 100 subjects, 50 patients were proteinuric and 50 patients had no proteinuria. The study participants' serum magnesium levels ranged from 1.2 to 2.7 mg/dL. Fourteen (28%) of proteinuric individuals had a serum magnesium level of less than 1.8 mg/dL. Hypomagnesemic patients had significantly higher urine albumin creatinine ratio (UACR) (2071 mg/g vs. 812 mg/g, P<0.001), significantly higher CRP (48 mg/L vs. 12 mg/L, P<0.001), and lower mean hemoglobin levels as well (10.4 g/dL vs. 10.91 g/dL, P= 0.044). Serum magnesium level showed negative correlation with UACR (r=−0.504, P<0.001), parathyroid hormone (r=−0.276, P=0.005), and CRP (r=−0.505, P<0.001). Conclusions Hypomagnesemia is a frequent electrolyte disorder in patients with CKD. Hypomagnesemia is independently associated with proteinuria. Hypomagnesemia is a risk factor of inflammation, anemia and hyperparathyroidism in pre-dialysis CKD population.